Super-algebraically convergent mathematical model of hollow waveguldes by Analytical Regularization Method - Tuchkin, Yury Alexanderovich; Suvorova, Olga; Dikmen, Fatih (My University, 2010)
An accurate and efficient simulation of hollow waveguides is in demand for many practical applications including those in the area of microwave engineering. But very many numerical methods produce ill conditioned matrix that getting correct results needs various numerical experiments (see, for example, [1], where the authors mentioned the instability of the method for the matrices of big sizes). Thus, some alternative numerically stable and efficient approach is in demand. Our algorithm based on Analytical Regularization Method [2]-[3], adopted in this paper for spectral problems, brings just such alternative to, at least, the hollow waveguide modeling considered herein. © 2010 IEEE. © 2010 Elsevier B.V., All rights reserved.
2010 International Kharkov Symposium on Physics and Engineering of Microwaves, Millimeter and Submillimeter Waves, MSMW'2010 -- Kharkov -- 81761
Keywords: Analytical regularization; Big sizes; Efficient simulation; Hollow waveguides; Ill-conditioned matrix; Microwave engineering; Numerical experiments; Spectral problem; Dynamic loads; Mathematical models; Millimeter wave devices; Optical systems; Radio waves; Submillimeter waves; Waveguides; Numerical methods